CULTURE-PRENEURSHIP PELAYANAN KEBIDANAN MELALUI IMPLEMENTASI TRI HITA KARANA PASCA PENDIDIKAN PROFESI DI WILAYAH KERJA IKATAN BIDAN INDONESIA PROVINSI BALI CABANG DENPASAR TAHUN 2023 - Sinta Javani,; I Made Sutajaya,; I Gusti Putu Sudiarta, (Jurnal Cakrawala Ilmiah, 2023)
The characteristics of midwifery services can be modified from the various approaches adopted. An approach that is a minimum service standard that refers to pure modern ways without any consideration of the local cultural approach. The local approach that can be taken is the Tri Hita Karana approach as local wisdom which will motivate people to come for a pregnancy check-up to get the results of monitoring the state of their pregnancy as well as a sense of comfort because there are three elements of peace that will be obtained in service with this philosophical approach that is local wisdom Balinese culture. This study uses the Tri Hita Karana approach as local wisdom in the implementation of Culture-Preneurship Midwifery Services Through the Implementation of Tri Hita Karana Post Professional Education in the Work Area of the Indonesian Midwives Association Bali Province Denpasar Branch in 2023. The method used in this study is a qualitative method, with a type of phenomenology in the form of a case study. Qualitative research data are data in the form of words, sentences, narratives, gestures, facial expressions, charts, pictures and photographs. This data can be divided into two types, namely empirical qualitative data and meaningful qualitative data. The results of this study are that the delivery of midwifery services refers to the standards of the midwifery profession. Based on existing standards, professional midwives will answer the needs of their clients by adapting to midwifery practices that are local wisdom which are evidence-based and provide greater benefits by adapting both.